1951
DOI: 10.1042/bj0480099
|View full text |Cite
|
Sign up to set email alerts
|

A new volumetric method for the determination of histaminase activity in biological fluids

Abstract: Different methods for the estimation of histaminase activity in biological fluids and many different units have been proposed by various workers. The methods described were either chemical (Zeller,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
11

Year Published

1954
1954
1971
1971

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 4 publications
0
11
0
11
Order By: Relevance
“…This conclusion was based on the finding of a strict parallelism between destruction of histamine and cadaverine by diamine oxidase preparations from different sources; competitive inhibition ofdiamine oxidase by histamine and cadaverine; and inhibition of the destruction of both substances by antagonists of diamine oxidase. More recently, however, Kapeller-Adler (1949, 1951 has questioned the identity of the two enzymes.All carbonyl reagents so far examined inhibit diamine oxidase, often in very low concentrations (Zeller, 1942). Zeller has shown that semicarbazide, thiosemicarbazide and hydroxylamine produce this effect, and has suggested that diamine oxidase itself contains carbonyl groups which interact with diamines and are blocked by carbonyl reagents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion was based on the finding of a strict parallelism between destruction of histamine and cadaverine by diamine oxidase preparations from different sources; competitive inhibition ofdiamine oxidase by histamine and cadaverine; and inhibition of the destruction of both substances by antagonists of diamine oxidase. More recently, however, Kapeller-Adler (1949, 1951 has questioned the identity of the two enzymes.All carbonyl reagents so far examined inhibit diamine oxidase, often in very low concentrations (Zeller, 1942). Zeller has shown that semicarbazide, thiosemicarbazide and hydroxylamine produce this effect, and has suggested that diamine oxidase itself contains carbonyl groups which interact with diamines and are blocked by carbonyl reagents.…”
mentioning
confidence: 99%
“…This conclusion was based on the finding of a strict parallelism between destruction of histamine and cadaverine by diamine oxidase preparations from different sources; competitive inhibition ofdiamine oxidase by histamine and cadaverine; and inhibition of the destruction of both substances by antagonists of diamine oxidase. More recently, however, Kapeller-Adler (1949, 1951 has questioned the identity of the two enzymes.…”
mentioning
confidence: 99%
“…It then rapidly returns within 3 or 4 days postpartum to the negligible values as found in normal non pregnant women (2).…”
mentioning
confidence: 90%
“…These were separately caged for 24 hr. without food before individual fasting blood-sugar levels were determined by the modified Folin-Malmros method (Landgrebe and Munday, 1954). They were injected subcutaneously at 7 day intervals with 0.5 ml.…”
Section: Methodsmentioning
confidence: 99%
“…Ti was omitted in 3 cats. Histaminase was prepared from fresh hog-kidney and its activity on the substrate was tested alone and in the presence of Ti and 2339 RP (2 x 10-' to 7 x l0-) according to Kapeller-Adler (1951). Antiadrenaline activity was examined on the blood pressure responses of atropinized spinal cats, cats anaesthetized with chloralose, rabbits anaesthetized with urethane, and dogs anaesthetized with sodium pentobarbitone or with sodium thiopentone followed by chlorbutol (1 ml.…”
Section: Methodsmentioning
confidence: 99%